2004
DOI: 10.1017/s0263593300001085
|View full text |Cite
|
Sign up to set email alerts
|

Late Archaean Kenogamissi complex, Abitibi Subprovince, Ontario, Canada: doming, folding and deformation-assisted melt remobilisation during syntectonic batholith emplacement

Abstract: The Kenogamissi complex represents a large exposure of folded Late Archaean crystalline crust exposed within the Abitibi Subprovince, Ontario, Canada. It is composed of an heterogeneous amphibolite-grade orthogneiss unit, and several generations of batholiths and plutons of tonalite, granodiorite and granite composition. Together, the various units represent granitic magmatism during the period from 2740 Ma to 2660 Ma. Structural mapping and petrographic studies were focused on the orthogneiss unit (2723 Ma), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…2710 Ma tonalitic plutons of the Kenogamissi complex (Kidd-Munro to Tisdale time) show a clear "deep" signature. The 2720-2740 Ma Gogama orthogneisses show a more heterogeneous signature, as can be expected from a complex of tectonically mixed rocks (Benn, 2004); at least part of the gneisses show a "deep" signature, and Benn and Moyen (2008) suggested that this would correspond to the "Deloro-age" portion of the orthogneisses. So, the "subduction" events in the Western Abitibi, as recorded by both plutonic and volcanic geochemical record, seem to occur in three to four discrete events, all of them short-lived (5-10 Ma) and superimposed on a "background" plume-like activity.…”
Section: Short-lived Archaean Subduction Episodes: the Geological Recordmentioning
confidence: 85%
“…2710 Ma tonalitic plutons of the Kenogamissi complex (Kidd-Munro to Tisdale time) show a clear "deep" signature. The 2720-2740 Ma Gogama orthogneisses show a more heterogeneous signature, as can be expected from a complex of tectonically mixed rocks (Benn, 2004); at least part of the gneisses show a "deep" signature, and Benn and Moyen (2008) suggested that this would correspond to the "Deloro-age" portion of the orthogneisses. So, the "subduction" events in the Western Abitibi, as recorded by both plutonic and volcanic geochemical record, seem to occur in three to four discrete events, all of them short-lived (5-10 Ma) and superimposed on a "background" plume-like activity.…”
Section: Short-lived Archaean Subduction Episodes: the Geological Recordmentioning
confidence: 85%
“…Although they are neglected rocks for sulfide base metals with the exception of nickel and chromium, such regional constraints can make greenstone belts particularly interesting in sulfide and gold research due to the potential for hosting sulfide and associated metal deposits (Benn 2004).…”
Section: Introductionmentioning
confidence: 99%